Management of Acute Kidney Injury and Extracorporeal Blood Purification Therapies During the COVID-19 Pandemic: The Italian SIN–SIAARTI Joint Survey (and Recommendations for Clinical Practice) - De Rosa, Silvia; Marengo, Marita; Romagnoli, Stefano; Fiorentino, Marco; Fanelli, Vito; Fiaccadori, Enrico; Brienza, Nicola; Morabito, Santo; Pota, Vincenzo; Valente, Fabrizio; Grasselli, Giacomo; Messa, Piergiorgio; et al. (Frontiers in Medicine, 2022)
Background and Aim The novel coronavirus disease 2019 remains challenging. A large number of hospitalized patients are at a high risk of developing AKI. For this reason, we conducted a nationwide survey to assess the incidence and management of AKI in critically ill patients affected by the SARS-CoV-2 infection. Methods This is a multicenter, observational, nationwide online survey, involving the Italian Society of Nephrology and the critical care units in Italy, developed in partnership between the scientific societies such as SIN and SIAARTI. Invitations to participate were distributed through emails and social networks. Data were collected for a period of 1 week during the COVID-19 pandemic. Results A total of 141 responses were collected in the SIN–SIAARTI survey: 54.6% from intensivists and 44.6% from nephrologists. About 19,000 cases of COVID-19 infection have been recorded in hospitalized patients; among these cases, 7.3% had a confirmed acute kidney injury (AKI), of which 82.2% were managed in ICUs. Only 43% of clinicians routinely used the international KDIGO criteria. Renal replacement therapy (RRT) was performed in 628 patients with continuous techniques used most frequently, and oliguria was the most common indication (74.05%). Early initiation was preferred, and RRT was contraindicated in the case of therapeutic withdrawal or in the presence of severe comorbidities or hemodynamic instability. Regional anticoagulation with citrate was the most common choice. About 41.04% of the interviewed physicians never used extracorporeal blood purification therapies (EBPTs) for inflammatory cytokine or endotoxin removal. Moreover, 4.33% of interviewed clinicians used these techniques only in the presence of AKI, whereas 24.63% adopted them even in the absence of AKI. Nephrologists made more use of EBPT, especially in the presence of AKI. HVHF was never used in 58.54% of respondents, but HCO membranes and adsorbents were used in more than 50% of cases. Conclusion This joint SIN–SIAARTI survey at the Italian Society of Nephrology and the critical care units in Italy showed that, during the COVID-19 pandemic, there was an underestimation of AKI based on the “non-use” of common diagnostic criteria, especially by intensivists. Similarly, the use of specific types of RRT and, in particular, blood purification therapies for immune modulation and organ support strongly differed between centers, suggesting the need for the development of standardized clinical guidelines.